Earth-abundant nontoxic direct band gap semiconductors for photovoltaic applications by ab-initio simulations. (15th September 2019) - Sreedevi, P.D.; Vidya, R.; Ravindran, P.
Highlights: First principles calculations on three earth-abundant nontoxic direct band gap semiconductors for photovoltaic applications. The structural, electronic and optical properties discussed. For the three compounds, the charge carrier effective masses are found along certain directions. Abstract: Direct band gap semiconductors with high optical absorption, high electrical conductivity, high carrier mobility, low reflectance and low recombination rate of charge carriers are needed for a variety of applications in solar energy conversion and optoelectronics. We have identified three ternary semiconductors Ca3 PN, NaBaP and ZrOS which have direct-band gap and other promising properties for solar energy applications. The prime novelty of this work mainly projects a detailed information on the electronic structure and optical properties for the three materials. From the first principles computational work and analysis, we have found that all the three materials with optimum band gap (~1.52 eV) value are having suitable absorption coefficient, extinction coefficient, optical conductivity and low reflectance in the visible region. Moreover, these materials are found to have low charge carrier effective masses and low recombination rates which can enhance carrier mobility and electrical conductivity. As a result, we will have three best non-silicon based direct band gap materials consisting of earth-abundant and non-toxic elements in the photovoltaic (PV) industry.